PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM PADA BELANJA MODAL - Jemparut, Maria Selcindya; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine whether local own source revenue and general allocation fund give influence to the capital expenditure on the government of districts / cities in East Java. The data is the local own source revenue and the general allocation fund is originated from the realization of the report of Local Budget of districts/cities in East Java in 2013-2015 periods, it has been obtained directly from the Audit Board of the Republic of Indonesia of East Java. The samples have been determined by using purposive sampling on districts /cities in East Java. Based on the predetermined criteria 108 samples. The hypothesis test has been done by using multiple linear regression analysis. The result of the research shows that: (1) local own source revenue give positive influence to the capital expenditure because when the acceptance of the local own source revenue is getting high, the capital expenditure which has been budgeted will be high; (2) general allocation fund give positive influence to the capital expenditure because when the acceptance of general allocation fund is getting high, the capital expenditure which can be allocated will be high.Keywords: local own source revenue, general allocation fund, capital expenditure